The impact of school violence on learning outcomes: experiences and challenges of learners at Hanover Park and Manenberg High Schools - October, Keziah October (Department of Social Development, 2025)
Research has established that adolescents' psychological well-being is significantly disrupted by exposure to violence (Sui et al., 2021; WHO, 2019). Youth, especially those in low socioeconomic environments, suffer both the psychological and physical consequences of violence. Violence within and around South African schools perpetuates a culture of violence, leading to educational delays and compromising youth safety. The surrounding community's social factors directly influence schools, increasing violence levels. School violence remains a pressing concern in many communities, with youth often exposed to a range of physical and psychological challenges. Youth exposed to persistent traumatic events, such as violence, tend to exhibit learning difficulties. Adequate learning necessitates a safe and conducive learning environment, yet the disruptive nature of school violence further exacerbates the challenges youth face, disrupting lessons and leading to curriculum delays, depriving youth of valuable educational opportunities (Child Trauma Academy, n.d). The purpose of this research was to qualitatively explore the experiences of how school violence affects the learning outcomes of youth in South African high schools. The study was guided by a qualitative research design, using non-probability sampling to recruit participants. In depth interviews were conducted with 16 high school youth who had experienced school violence. The study found that high school youth face daily exposure to various forms of school violence. One of the key challenges faced by the participants was their persistent fear of being victimized by violence in school and while travelling to and from school. The accounts provided by the participants depict a disconcerting reality in which school violence instils fear, vulnerability, and disruption, collectively jeopardizing the well-being and educational progress of high school youth in Cape Town. These findings underscore the pressing urgency of implementing measures to address these multifaceted challenges and create a safer and more conducive learning environment for the affected youth. Based on the findings of this study, it is recommended that a holistic approach be advocated, one that explores the challenges affecting youth across different microsystems in their lives. Collaborative partnerships among stakeholders, including community members, educational professionals, and mental health experts, are essential for formulating and promptly implementing a policy proposal that addresses the various challenges affecting the learning outcomes of youth. Furthermore, stakeholders and policymakers should introduce comprehensive and effective monitoring and evaluation mechanisms to provide constructive feedback. Moreover, there is an urgent need to promote safety and security in schools, foster a more supportive learning environment, and raise awareness about the effects of trauma on learning. Additionally, the study underscores the urgency of professional support for youth affected by school violence and advocates for the implementation of adequate support and care within South African schools.